Enhancing Adaptive Overcurrent Protection in Multi-Loop Distribution Networks with Distributed Generation Using Genetic Algorithms - Arnawan Hasibuan; Fahrian Roid; Armen Abta; Misbahul Jannah; Dedi Fariadi; Fakhruddin Ahmad Nasution (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
Electrical energy is something that everyone needs. The increase in the use of electrical energy will increase the transmission and distribution system of electrical energy, so the electrical energy distribution system must be more reliable. Adding Distributed Generation (DG) to the distribution system can improve reliability and power quality issues. To overcome the influence of DG, a new optimization setting is needed to account for the presence of Distributed Generation. This study aims to simulate a protection system with the right relay operation time to minimize the impact of interference and apply the Genetic Algorithm method in the relay coordination setting on a multi-loop distribution network with Distributed Generation. In this study, the development will be carried out using the IEEE 9-Bus multiloop plant distribution system with the application of Distributed Generation using a Genetic Algorithm. The method in this study begins with creating a single-line diagram on ETAP, followed by the placement and determination of forward and reverse relays. Furthermore, the steps include dividing and determining loops I, II, and III for the Isc generation value in each loop. The optimization process using the Genetic Algorithm can be carried out after the Isc value of each loop is obtained. After reaching the maximum iteration value, the TDS and Ipickup values result from optimization. The value is then converted into a time domain. The genetic algorithm results with a maximum iteration value of 1500 show that the protection system coordinates more optimally and efficiently, as reviewed from the cut-off sequence and time delay value in the event of a disturbance. The total time delay value in the Genetic Algorithm calculation is 3.6027 seconds. The minimum total time delay value is the more optimal the protection system coordinates.